Senso de posição articular está bilateralmente reduzido para abdução e flexão do ombro em indivíduos hemiparéticos crônicos - Santos, Gabriela Lopes dos (2014)
Background: The stroke is the leading cause of adult disability in the world. One of the main complaints of individuals post-stroke refers to the loss of function of the upper limb, as evidenced during the performance of activities of daily living. This difficulty may be related to an important component of sensorimotor control, joint position sense, a submodality of proprioception. The relationship of sense of joint and the difficulties of upper limb movements are not clear in the literature. Objectives: To investigate whether the joint position sense of both shoulders of chronic hemiparetic is altered during the abduction and flexion, and whether there is any correlation between joint position sense and sensorimotor performance in these subjects. Methods: The study included 13 subjects with chronic hemiparesis due to ischemic stroke and 13 healthy subjects matched for gender and age. The proprioception was assessed using an isokinetic dynamometer and by joint sense position. The variable calculated was absolute error for shoulder abduction and flexion at the 30° and 60°. The motor performance was assessed by the upper extremity of the Fugl-Meyer Motor Assessment Scale. For the comparison between paretic, nonparetic and control limbs was utilized Kruskal Wallis test following post-hoc of Mann-Whitney with Bonferroni adjustment. For the correlation were used the Spearman. Results: No difference was found between the paretic and non-paretic limbs in both movements at 30o and 60o (p>0.05). But higher values of absolute error for both paretic and nonparetic limbs compared to control were observed during abduction at 30o (p <0.01) and at 60o (p=0.03 and p=0.04, respectively). During flexion, higher values of absolute error was observed in paretic limbs compared to control at 30o (p=0.01) and also at 60o (p=0.02). Non paretic limbs presented higher values of absolute error only at 30o, when compared to control (p=0.01). Total absolute error was inversely correlated to sensibility and proprioception Fugl-Meyer Motor Assessment Subscales (EFM). Absolute error also was directly correlated right hemisphere injury. Furthermore, absolute error was to shoulder´s subluxation during abduction. Conclusion: The joint position sense is affected in both shoulders of chronic post-stroke ischemic hemiparetic subjects during flexion and abduction. These proprioceptive deficits of the paretic limb are correlated to subscale score of proprioception and sensibility EFM, shoulder´s subluxation and damaged hemisphere.